DNA/BSA interactions and cytotoxic studies of tetradentate N,N,O,O Schiff base copper(II) complexes - Mijatović Aleksandar; Caković Angelina Z.; Lolić Aleksandar; Sretenović Snežana; Živanović Marko N.; Šeklić Dragana S.; Bogojeski Jovana; Petrović Biljana V. (Journal of the Serbian Chemical Society, 2023)
Three Schiff base Cu(II) complexes, (N,N’-bis(acetylacetone)propylenediimine) copper(II) complex, [Cu(acac2pn)] (1), (N,N'-bis-(benzoylacetone) propylenediimine)copper(II) complex, [Cu(phacac2pn)] (2) and (N,N’-bis- -(trifluoroacetylacetone)propylenediimine)copper(II) complex, [Cu(tfacac2pn)] (3), were used to investigate the interactions with calf thymus DNA (ct-DNA) and bovine serum albumin (BSA) using the electronic absorption and spectroscopic fluorescence methods. UV–Vis absorption studies showed that studied complexes interact with DNA molecule and exhibit moderate binding affinity. Fluorescence studies of complexes 1–3 also showed a possibility for DNA intercalation as well as a relatively high binding ability toward BSA. Among the tested complexes, the highest affinity for DNA and BSA molecules was shown by complex 1. Cytotoxic analyses, performed on human colorectal carcinoma HCT-116 and healthy lung fibroblast MRC-5 cell lines, showed that complex 2 exhibited activity on both cell lines, while complexes 1 and 3 did not show any activity.